2023
DOI: 10.1021/acschembio.3c00376
|View full text |Cite
|
Sign up to set email alerts
|

RyR2 Binding of an Antiarrhythmic Cyclic Depsipeptide Mapped Using Confocal Fluorescence Lifetime Detection of FRET

Jaroslava Šeflová,
Jacob A. Schwarz,
Abigail N. Smith
et al.

Abstract: Hyperactivity of cardiac sarcoplasmic reticulum (SR) ryanodine receptor (RyR2) Ca 2+ -release channels contributes to heart failure and arrhythmias. Reducing the RyR2 activity, particularly during cardiac relaxation (diastole), is a desirable therapeutic goal. We previously reported that the unnatural enantiomer (ent) of an insect-RyR activator, verticilide, inhibits porcine and mouse RyR2 at diastolic (nanomolar) Ca 2+ and has in vivo efficacy against atrial and ventricular arrhythmia. To determine the ent-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Our in vitro assays suggest that, like ent-1, ent-B1 directly binds to RyR2 and produces incomplete inhibition, unlike recently identified RyR2 inhibitory compounds (chloroxylenol, methyl orsellinate, and riluzole) which produce complete RyR2 block (Takenaka et al, 2023). ent-B1 likely acts as a negative allosteric modulator of channel function, similar to ent-1, for which we recently identified a putative binding site (Seflova et al, 2023). ent-B1's combination of sub-micromolar potency and partial channel inhibition is ideal for our target, as a stronger inhibition of RyR2 could be fatal given its central role in physiologic excitation-contraction coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro assays suggest that, like ent-1, ent-B1 directly binds to RyR2 and produces incomplete inhibition, unlike recently identified RyR2 inhibitory compounds (chloroxylenol, methyl orsellinate, and riluzole) which produce complete RyR2 block (Takenaka et al, 2023). ent-B1 likely acts as a negative allosteric modulator of channel function, similar to ent-1, for which we recently identified a putative binding site (Seflova et al, 2023). ent-B1's combination of sub-micromolar potency and partial channel inhibition is ideal for our target, as a stronger inhibition of RyR2 could be fatal given its central role in physiologic excitation-contraction coupling.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, we reported that its non-natural enantiomer ( 1 ) exhibits activity at mammalian ryanodine receptor 2 (RyR2), while nat -verticilide was inactive, recording an evidently unprecedented case where all detectable activity against a specific target is harbored by the non-natural enantiomer of a natural product. 3 , 4 RyR2 is a target for antiarrhythmic development, and selective inhibitors promise to develop a more complete picture of its role in heart disease. 5 7 We have since discovered a second example of activity harbored entirely by the non-natural enantiomer in the antiarrhythmic ent -verticilide B1—the 18-membered oligomer of 1 .…”
Section: Introductionmentioning
confidence: 99%